Effect of harvesting stage on plant growth characteristic of Andrographis paniculata - Azis, Nur Amiraa (2015)
Hempedu bumi (Andrographis paniculata) is widely used in traditional medicine and is one of the local medicinal herbs identified increasing in medical world. The information on the optimum harvesting stage of A. paniculata for optimum plant growth characteristics and biomass yield for commercial production is still lacking. A. paniculata was planted at Vegetable Unit, Universiti Putra Malaysia. This experiment was conducted to determine the effects of harvest time on plant growth characteristics of A. paniculata. The plant was harvested at 7, 8, 9 and 10 weeks after transplanting. The experiment was conducted in a randomized complete block design (RCBD) with four replications. After harvest, the plants were taken to the Postharvest Laboratory, Department of Crop Science, Faculty of Agriculture, Universiti Putra Malaysia for further analysis. The parameters that were evaluated throughout this experiment were plant height, plant canopy diameter, chlorophyll content, leaf area, and fresh and dry weight of aerial yield plant part, leaves and stem.